Beyond the Title: An In-Depth Exploration of the Leadership Experiences and Styles of Sangguniang Kabataan Presidents - Pasicaran-Escleto, Grezel; Cabatingan, Albim Y.; Polinar, Mark Anthony N.; Delantar, Alexander Franco A. (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Youth leadership is essential for nation-building, providing early exposure to governance and community service. The Sangguniang Kabataan (SK) offers young people a platform to take on leadership roles in local government, allowing them to engage in decision-making and implement youth-focused programs. The experiences of SK Presidents often extend beyond their official duties, featuring various challenges, opportunities, and personal growth. This study explored the lived experiences of leadership among the Sangguniang Kabataan Presidents of Pangantucan, Bukidnon. The researchers used narrative inquiry or phenomenology to highlight the exploration of the key informants' lived experiences to understand the issue.  It sought to answer the domains of inquiry: the lived experiences of the Sangguniang Kabataan officials on their leadership styles, the essence or meaning of their lived experience, and the factors that can improve or deteriorate their leadership. To collect data, the researchers used the descriptive-qualitative method. The study's eight key informants are the current SK President of Pangantucan, Bukidnon, where the study was conducted, and key informants who serve the public. The researchers were the primary instrument, a validated interview guide, and audio recordings were transcribed into written text. The researcher gathered significant statements from the outputs of the key informant interviews during data analysis, and five themes were generated. These themes served as feeders to the study's production. The study identified leadership challenges faced by key informants in the Sangguniang Kabataan of Pangantucan, Bukidnon. A proposed leadership model aims to address these challenges and promote effective governance in the barangay.